THE EXPECTATIONS AND SATISFACTION LEVELS OF ACADEMIC JOURNALS EDITORS IN THEIR RELATIONSHIPS WITH UNIVERSITIES - Mainardes, Emerson Wagner; Alves, Helena; Raposo, Mario (Contextus - Revista Contemporânea de Economia e Gestão, 2015)
From the perspective of the Stakeholder Theory, the objective of this paper was to, initially, identify and classify by importance the expectations of editors from scientific journal that are indexed in ISI about its relationship with the universities. After that, the objective was to measure the satisfaction levels of the same editors as to its relationship with universities in general. 276 answers were obtained and the results showed that the satisfaction of the editors with the universities comes from the offer, by the universities, of the adequate facilities for research, including scientific research in the degree programs, encouragement for having and funding scientific events at the university, and of the encourage by the university for their students to participate in research projects.